(untitled) (Jurnal Rekayasa Mesin dan Inovasi Teknologi, 2022)
Surface roughness characteristics are influenced by several cutting parameters including spindle speed, depth of cut, and tool path. One of the parameters that affect the surface roughness in the machining process is spindle speed. This study uses quantitative methods with stages of literacy, observation, and field documentation. The independent variables are variations in spindle speed, namely 500 rpm, 800 rpm, 1,200 rpm, feeding speed of 200 mm/min, and using 4 measurement points. The dependent variable is the roughness value of the spindle speed variation against AISI 4140 carbon steel and the controlled variable is the feed depth of 1 mm, the type of face mill chisel, and the standard roughness that has been set. In this study, the average roughness value was found at the spindle speed of 500 (rpm) with a value of 0.628 µm, the spindle speed of 800 (rpm) with a value of 0.361 µm, and the spindle speed of 1,200 (rpm) with a roughness value of 0.17 µm. What affects the surface roughness of the AISI 4140 material is the faster the spindle rotation rate, the smaller the roughness value on the surface of the AISI 4140 material. Keywords: Spindle speed, AISI 4140, (Computer Numerical Control) CNC, Surface roughness.